2022
DOI: 10.1371/journal.pone.0267817
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide suicide mortality trends by firearm (1990–2019): A joinpoint regression analysis

Abstract: Introduction Suicide by firearm is a major public health problem in many countries. But, studies that investigated the mortality of suicide by firearm on a global scale are still limited. The aim of this study was to assess the global, regional and national trends in mortality of suicide by firearm from 1990 to 2019. Method Mortality data of suicide by firearm was presented using the age-standardized rates (ASRs, expressed per 100,000). Joinpoint regression analysis was used to assess trends of mortality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, we did not differentiate between car exhaust suicides and other gases. Similarly to Ilić et al (2022), we too found that suicides by firearms was a male-dominated method and more often used by older persons. Firearm-specific suicide rates may be at least to some extent related to the accessibility.…”
Section: Discussionmentioning
confidence: 61%
“…However, we did not differentiate between car exhaust suicides and other gases. Similarly to Ilić et al (2022), we too found that suicides by firearms was a male-dominated method and more often used by older persons. Firearm-specific suicide rates may be at least to some extent related to the accessibility.…”
Section: Discussionmentioning
confidence: 61%
“…In fact, the most common means of suicide in the United States is death by firearms. Other countries with high firearm possession rates, such as Uruguay and Montenegro, have also reported high of suicide by firearms [ 4 , 8 ]. Meanwhile, in countries that do not have high firearm possession rates, such as Asian or Nordic countries, poisoning by pesticides is the most common means of suicide.…”
Section: Introductionmentioning
confidence: 99%